1H NMR-based metabonomics revealed protective effect of Naodesheng bioactive extract on ischemic stroke rats. (20th June 2016) - Luo, Lan; Zhen, Lifeng; Xu, Yatao; Yang, Yongxia; Feng, Suxiang; Wang, Shumei; Liang, Shengwang
Abstract: Ethnopharmacological relevance: Stroke is a leading cause of death and disability in the world. However, current therapies are limited. Naodesheng, a widely used traditional Chinese medicine prescription, has shown a good clinical curative effect on ischemic stroke. Also, Naodesheng has been suggested to have neuroprotective effect on focal cerebral ischemia rats, but the underlying molecular mechanism remains unclear. Aim of the study: The present study was designed to evaluate the effect of Naodesheng bioactive extract on the metabolic changes in brain tissue, plasma and urine induced by cerebral ischemia perfusion injury, and explore the possible metabolic mechanisms by using a 1 H NMR-based metabonomics approach. Materials and methods: A middle cerebral artery occlusion rat model was established and confirmed by the experiments of neurobehavioral abnormality evaluation, brain tissue TTC staining and pathological examination. The metabolic changes in brain tissue, plasma and urine were then assessed by a 1 H NMR technique combined with multivariate statistical analysis method. Results: These NMR data showed that cerebral ischemia reperfusion induced great metabolic disorders in brain tissue, plasma and urine metabolisms. However, Naodesheng bioactive extract could reverse most of the imbalanced metabolites. Meanwhile, it was found that both the medium and high dosages of Naodesheng bioactive extract were more effective on the metabolic changes than the low dosage, consistent with histopathological assessments. Conclusions: These results revealed that Naodesheng had protective effect on ischemic stroke rats and the underlying mechanisms involved multiple metabolic pathways, including energy metabolism, amino acid metabolism, oxidative stress and inflammatory injury. The present study could provide evidence that metabonomics revealed its capacity to evaluate the holistic efficacy of traditional Chinese medicine and explore the underlying mechanisms. Graphical abstract: